STRATEGI CV. RUMAH TAMADUN DALAM PRODUK OLAHAN LIMBAH LIDI SAWIT KE AMERIKA SERIKAT - Dewi Rizqianti; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT CV. Rumah Tamadun MSME business unit engaged in handicrafts. This study aims to describe CV strategies. The House of Civilization is in the process of internationalization. This study also describes the implementation of factors related to the internationalization process of CV. Rumah Tamadun. This research uses qualitative methods, with data collection techniques through primary data collection sourced from field research and through secondary data collection through literature studies sourced from several books, journals, articles, websites and using the concept of Penta Helix and Internationalization theory. The result of this paper is that CV. Rumah Tamadun has a strategy for the internationalization process, namely a product marketing strategy that has a correlation with the elements of the Penta Helix indicator. Internationalization of CV. Rumah Tamadun products in America are marketed through KEREIN Production and e-commerce. The concept of Penta Helix and its implementation in the internationalization process of CV. Rumah Tamadun in the form of a combination of elements of Academia (Conceptor), Business Player (Enabler), Community (Accelerator), Media (Expander). Government (Regulator). Keyword : CV. Rumah Tamadun, Internationalization, Palm Stick Bag, Penta Helix